Projecting sound effects in gaming - Wang, Xuan. (2011)
This Paper elaborates the design and development of an analog circuit system which produces directional sound for the purpose of projecting sound effects in games. Such system is able to modulate audio signal from various game controllers and emits the modulated signal via ultrasonic emitter to form a parametric speak array. The reproduced sound becomes highly directional in air and will eventually create a virtual sound source at the place where the wave is reflected.